Design space determination and process optimization in at-scale continuous twin screw wet granulation. (9th June 2019) - Liu, Huolong; Ricart, Brendon; Stanton, Courtney; Smith-Goettler, Brandye; Verdi, Luke; O'Connor, Thomas; Lee, Sau; Yoon, Seongkyu
Highlights: A continuous twin screw granulation process was optimized via quality by design approach. Effect of process variables of TSWG on granule properties and tablet properties was investigated. Design space based on granule diameter and tablet disintegration time was determined. Application of DS in selecting operating condition to improve probability of product quality. Abstract: At-scale industrial continuous twin screw wet granulation process was analyzed and optimized via design of experiment (DoE). The Box-Behnken method was selected to investigate the influence of key process variables on granule properties and tablet properties. The effects of the key process variables were analyzed. The experimental results have demonstrated that both the granule properties and tablet properties are influenced by the throughput, the screw speed and the screw element. Particularly, the screw element type and the milling process were found having significant effects on tablet tensile strength and disintegration time. The design space (DS) based on volume average granule diameter (Y4 < 800 µm) and tablet disintegration time (Y8 < 4 min) was determined using Monte Carlo simulations. Validation experiments have shown the robustness of the DS. A case study of the DS application is presented. It was demonstrated how to select optimum working conditions of key process parameters based on the DS. Graphical abstract: Image, graphical abstract